The properties of poly(latic acid) (PLA)/hydroxyapatite (FsHAp) composite prepared through solvent casting techniques - Peremel, Santhiya; Jaafar, Che Nor Aiza; Zainol, Ismail; Mohd Ariffin, Mohd Khairol Anuar; Chen, Ruey Shan (Universiti Putra Malaysia, 2023)
In this study, the properties of composites produced using solvent casting technique from poly(lactic acid) (PLA) and fish scale hydroxyapatite (FsHA) were investigated. Some amount of FsHAp powders (from 10 to 70 wt) were added to the PLA solution and stirred for eight hours after the PLA was dissolved in the dichloromethane (DCM) solvent. The homogeneous mixture of PLA and FsHA was poured into the metal mould and dried in the oven for 4 hours to produce a dried PLA/FsHA composite sheet. The PLA/FsHA composite sheet with different FsHA filler contents was successfully prepared. These composites were characterised by Fourier transform infared spectroscopy (FTIR), differential scanning calorimetry (DSC), tensile tester and scanning electron microscope (SEM). It can be seen that by addition of 50 wt FsHA filler contents gave the highest Young’s Modulus and tensile strength values of 2114.8 MPa and 23.3 MPa, respectively due to effective interaction between fillers and matrix. The melting point of pure PLA, which was 147 °C increased to 149 °C when it was loading with 30 wt FsHA and this enhancement may attributed to the capacity of natural FsHA to encourage surface contact between PLA matrix. The DSC result was consistent with the FTIR result which demonstrated that the peaks' shifting implied some degree of chemical interaction between the matrix and FsHA. From SEM analysis, it proved good distributions of FsHA fillers in the matrix of PLA/FsHA composites and this indicated that the composite has potential to be used in biomedical applications.